Repertoire Denny Novita dan Transformasi Kisah Gajah Mada dan Pitaloka dalam Novel Kembang Seruni - Widihastuti, Rahma Ari (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
In the Kitab Pararaton, the relationship between Gajah Mada and Dyah Ayu Pitaloka does not describe a special relationship. However, there is a different meaning from the perspective of the reader which is then appreciated as a new work. This study aims to compare the story of Gajah Mada and Pitaloka in the Kitab Pararaton with